Hubungan Intake Cairan Dengan Peningkatan Tekanan Darah Pada Pasien Gagal Ginjal Kronik (GGK) Yang Menjalani Hemodialisa di Rumah Sakit Tk. III dr. Reksodiwiryo - Reni Trevia; Erni Musmiler (Jurnal Amanah Kesehatan, 2023)
Excess fluid intake in patients with chronic renal failure undergoing hemodialysis will cause complications which lead to death.. This study aims to determine the relationship of fluid intake with increased blood pressure in patients with chronic renal failure undergoing hemodialysis in Tk Hospital. III Reksodiwiryo Padang. his type of research uses the Correlation Analytical Observational method, with the Cross Sectional Study design. This study was conducted in the Hemodialisa Hospital of Tk. III Dr. Reksodiwiryo Padang. population of 49 patients with chronic renal failure undergoing hemodialysis. The sampling technique uses Total Sampling. The results of univariate research on increasing systolic blood pressure (57%), diastole (36.7%) and fluid intake (water / eating + drinking), medicine / medicine, metabolic water). Bivariate results showed that there was a relationship between fluid intake and systolic blood pressure (p = 0.18) and there was a relationship between fluid intake and diastolic blood pressure (p = 0, 13). The conclusion of the study is that there is a relationship between fluid intake and an increase in blood pressure in patients with chronic renal failure undergoing hemodilysis and is advised to be an input in efforts to improve health services at the hospital. II Dr. Reksodiwiryo Padang, nurses run more health education about fluid intake monitoring patients with chronic renal failure patients undergoing hemodialysis to avoid problems with limiting fluid intake. Keywords: fluid intake; increased blood pressure; chronic renal failur